Tenofovir DF/emtricitabine and efavirenz combination therapy for HIV infection in patients treated for tuberculosis: the ANRS 129 BKVIR trial. (17th December 2015) - Lortholary, Olivier; Roussillon, Caroline; Boucherie, Céline; Padoin, Christophe; Chaix, Marie-Laure; Breton, Guillaume; Rami, Agathe; Veziris, Nicolas; Patey, Olivier; Caumes, Eric; May, Thierry; Molina, Jean-Michel; et al.
Abstract : This multicentre, non-comparative pilot trial showed that tenofovir DF/emtricitabine and efavirenz, given once daily to patients already being treated for TB, could provide a simplified, effective and well-tolerated treatment regimen for first-line treatment of HIV infection. Abstract: Background: HIV-infected patients with TB need simplified, effective and well-tolerated antiretroviral regimens. Methods: The French ANRS 129 BKVIR open trial evaluated the once-daily tenofovir DF/emtricitabine and efavirenz combination, started within 12 weeks after TB treatment initiation, in antiretroviral-naive HIV-1-infected patients. Success was defined as an HIV-1 RNA <50 copies/mL and TB cure at 48 weeks. Results: TB was confirmed microbiologically (90%) or histologically (10%) in 69 patients (71% male; median age 43 years; 54% born in Africa). The median time between TB treatment initiation and antiretroviral therapy was 8 weeks (range 1–22 weeks). At baseline, median HIV-1 RNA was 5.4 log10 copies/mL and median CD4 cell count 74 cells/mm 3 . In the ITT analysis, combined success at week 48 was achieved in 57/69 patients (83%, 95% CI 74–92). Twelve patients did not achieve virological success, and TB was not cured in one of them. Among the 47 patients who fully adhered to the strategy, the success rate was 96% (95% CI 90–100) and was not affected by low rifampicin and isoniazid serum concentrations. Forty-nine serious adverse events were reported in 31 patients (45%), and 11 led to antiretroviral drug interruption. All adverse events resolved. The immune reconstitution inflammatory syndrome occurred in 23 patients (33%, 95% CI 22–44), and was associated with a low baseline BMI ( P = 0.03) and a low haemoglobin level ( P = 0.02). Conclusion: These results support the use of tenofovir DF/emtricitabine and efavirenz combination therapy for HIV infection in patients with TB.